2009
DOI: 10.1001/archoto.2009.94
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Localization of the Lacrimal Sac

Abstract: Objective: To optimize the approach to the lacrimal sac during intranasal dacryocystorhinostomy.Design: Microscopic measurement of anatomical landmarks in cadaver sagittal head sections. Setting:The anatomy department of a large university hospital.Participants: Twenty adult cadaver sagittal head sections (12 right and 8 left) fixed with 10% formaldehyde solution were evaluated.Intervention: During endoscopic dissections, the maxillary line, lacrimomaxillary suture, nasolacrimal duct, and lacrimal sac were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
3
27
1
1
Order By: Relevance
“…Relevant landmarks are required for better localization of the NLD and lacrimal sac on the lateral nasal wall. The maxillary line and axilla of the middle nasal concha are the most frequently used anatomical landmarks [3,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant landmarks are required for better localization of the NLD and lacrimal sac on the lateral nasal wall. The maxillary line and axilla of the middle nasal concha are the most frequently used anatomical landmarks [3,17].…”
Section: Discussionmentioning
confidence: 99%
“…Orhan et al [17] observed 20 hemisectioned heads and reported overlap of the maxillary line with the lacrimal sac at a ratio of 18:20 (90%). However, in this study, overlap of the maxillary line with the NLD was observed in only 24 of 36 cases (67%).…”
Section: Discussionmentioning
confidence: 99%
“…Distances from the NLD opening, anterior nasal spine, maxillary sinus ostium, uncinate process, and other landmarks have been reported previously for assisting with localization of the lacrimal sac (Kim et al, 2012;Orhan et al, 2009;Tatlisumak et al, 2010;Yung and Logan, 1999). The maxillary line serves as a consistent anatomical landmark for endoscopic DCR surgery.…”
Section: Surgical Anatomymentioning
confidence: 71%
“…The maxillary line is an important landmark for uncinectomy, endoscopic DCR, and endoscopic orbital decompression (Chastain et al, 2005;Metson et al, 1994;Kingdom and Durairaj, 2006;Sindwani and Metson, 2008;Orhan et al, 2009;Shams et al, 2012). It is a curvilinear eminence on the lateral nasal cavity wall which projects from the axilla of the middle turbinate to the dorsum of the anterior attachment of the inferior turbinate.…”
Section: The Maxillary Linementioning
confidence: 99%
See 1 more Smart Citation